STRATEGI PEMASARAN SAYURAN HIDROPONIK (Studi Kasus Pada CV Casafarm Bandung) - Almas Dwi Nurshadrina; Zumi Saidah (Universitas Galuh, 2023)
iThis istudy iaims ito identify the Vegetable marketing strategy to be implemented by CV. Casafarm Bandung. CV. Casafarm is a hydroponic farming business entity ilocated iin ithe icity iof iBandung, iWest iJava. CV. Casafarm is a privately owned company engaged in agriculture, especially in the field of hydroponic cultivation. iThe iresearch imethod iused iis iqualitative iwith ia idescriptive iresearch idesign. iData icollection itechniques iused iin ithis istudy iwere iinterviews iand idocumentation. iThis istudy iuses several analytical designs, namely environmental analysis, iIFAS (Internal iStrategic iFactor iSummary) Matrix Analysis, iEFAS i (External iStrategic iFactor iSummary) Matrix Analysis, iInternal-iExternal Matrix Analysis and SWOT Matrix Analysis. The itriangulation iused iin ithis iresearch iis isource itriangulation, itechnique itriangulation iand itime itriangulation. iThe results of calculations related to the company's internal and external factors obtained results, namely 1) Strength (strength) of 2.64; 2) Weakness is worth 0.44; 3) Opportunities (opportunities) are 2.36; and Threats (threats) are worth 0.56. CV development policy direction. Casa Farm Hydroponics is in a condition of rapid growth strategy where ibased ion ithe iresults iof the SWOT calculation ithat ihas ibeen icarried iout with a score of S > O, which means that the strength is greater than the existing opportunities